Pengaruh Profitabilitas, Likuiditas, Leverage, dan Ukuran Perusahaan Terhadap Kebijakan Dividen pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2018-2021 - Cindy Veronica Tehresia; Joiceline Yangga; Keumala Hayati; Wenny Anggeresia Ginting (Universitas Batanghari Jambi, 2023)
This study aims to determine the effect of profitability, liquidity, leverage, and company size on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The data used is sourced from financial data on the Indonesia Stock Exchange through the website www.idx.co.id and has been selected based on predetermined criteria. The population used in this study were manufacturing companies, totaling 214 companies, using purposive sampling, the samples obtained were 40 companies. With this research, it is hoped that it can become a science to help further researchers as well as students or the general public who need a source of information. The results of the study show that simultaneously the variables profitability (ROA), liquidity (CR), leverage (DER), and company size (SIZE) have a significant effect on dividend policy (DPR) in manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2021 period.